56 Effects of creep feed supplementation and sire breed on the post-weaning performance of replacement doelings. (28th November 2020) - Hayes, Emily G; Stevens, Lauren; Thomas, Shaneqwa; Hurt, Kaylee; Browning, Richard
Abstract: This study examined the influence of creep feeding and sire breed on post-weaning replacement doeling traits. Over 3 years, doelings by Kiko, Myotonic, Spanish and Savanna sires were creep-fed (CF; n = 116) for 60 d or not creep-fed (NC; n = 117). Sire breeds were balanced across creep treatments. Doelings were weighed at 3 mo old (weaning) and various postweaning ages. Doelings entered the breeding herd at 18 mo of age and fitness traits recorded. At 3-, 6-, and 12-mo of age CF (14.7 ± 0.6, 19.3 ± 1.2, and 24.6 ± 0.9 kg, respectively) were heavier (P < 0.05) than NC (13.8 ± 0.6, 17.9 ± 1.2, and 23.6 ± 0.9 kg, respectively). Treatment did not affect 18-mo weights. Sire breed did not affect 3-mo weight. Sire breed influenced (P < 0.05) 6-, 12-, and 18-mo weights. Myotonic-sired doelings were lightest (P < 0.05) and Kiko-sired doelings were heavier (P < 0.05) than Savanna-sired. Breed x treatment interacted (P < 0.05) for survival to 18 mo of age. Kiko-sired CF doelings had a higher (P < 0.05) survival rate than Savanna-sired CF (88.6 ± 6.0% vs. 44.6 ± 11.5%). Breed did not affect survival rate (P> 0.05) within the NC group. As a main effect, CF had a higher (P < 0.05) survival rate than NC (81.5 ± 6.3% vs. 65.6 ± 8.7%). Sire breed affected (P < 0.05) reproductive output. Cumulative kid crop weaned across the first 2 breeding years for the whole weaned doeling population was higher (P < 0.05) for Myotonic- and Kiko-sired (1.4 and 1.2 ± 0.2 kids) does than Savanna-sired (0.5 ± 0.1 kids). Creep feeding did not affect reproductive output. Creep feed supplementation and sire breed influenced post-weaning doeling weights. Only sire breed affected reproductive performance of the young does.